Biotechnological breakthrough to cattail fiber as an ultra-efficient natural oil sorbent - Sergey Gorbachev; Olga Gennadievna Gorovykh; Ashish Mani; Abhishek Dixit; Baurzhan Alpysovich Alzhanov; Jun Yan (Scientific Reports)
Abstract Most synthetic oil sorbents are expensive, environmentally unsafe, difficult to regenerate and utilize, therefore it is preferable to use natural oleophilic and hydrophobic materials. In this paper we have studied the mechanism and kinetic parameters of the sorption process by cattail fiber as natural oil sorbent, its performance characteristics. We show that it has a high sorption capacity for many oil products, high sorption rate (less than 1 min), long buoyancy (more than 30 days), the possibility of multiple regeneration (more than 50 cycles). This finding allow us to consider cattail fibers as a highly effective natural material for the elimination of emergency oil spills. To solve difficult problem of collecting spent cattail fiber, we have designed of new technical solution such as a special adhesive collector. For the regeneration of spent cattail fiber, we have studied advantages and disadvantages various biotechnological methods and devices such as: squeezing on mechanical rollers, centrifugation, vacuum extraction and squeezing using a water press. Our laboratory installation demonstrates, for the first time, the technological feasibility and great efficiency of water press method for the regeneration of fibrous sorbents in real-world environmental emergency response conditions.